Penguatan Budaya Gotong Royong Sebagai Strategi Pemeliharaan Infrastruktur Lingkungan Melalui Pembersihan Jalan Dan Drainase Di Nagari Sungai Jambur Kota Solok - Nofrion .; Siti Khadijah; Febi Akrida; Muhammad Dzaky Alfaiz; Ardi Karel Wesley Sembiring (CV. ITTC INDONESIA, 2026)
Community-based environmental maintenance is an importanst effor to support environmental sustainability and improve the quality of public infrastructure. One of the activities routinely carried out by ommunity of Nagari Sungai Jambur, Solok City, is the annual mutual cooperation program foccusing on road and drainage cleaning. This community servie activity aims to strengthen the culture of mutual cooperation while imroving enviromental cleanliness and drainage functionality. The methods used include observation, coordination with local stakeholders, implementation of collecctive cleaning activities, and evaluation of outcomes. The result indicate that the activity seccesfully reduced waste accumulation, imtpoved water flow in drainage channels, enhanced environmental cleanliness, and strengthened social cohesion among ccommunity members. Futhermore, the activity contibuted to increasing public awarness regarding environmental conservation and sustainable infractructure maintancce. Therefore, annual mutual cooperation activities can serve as an effective stratefy for fostering community participation and environmental stewardship.